Does Archer’s Drinking Fit Within the NHS Guidelines? - Smith, Katherine (Journal of Interdisciplinary Science Topics, 2017)
This paper looks at the alcohol consumption of Sterling Archer, and calculates the average unit consumption per week to calculate whether Archer's drinking fits within the recommended unit intake as given by the NHS. It has been determined that based on the drinks seen during screen time (not including flashbacks or empty bottles next to him at the start of episodes) on average Archer drinks 10.10 units per week, meaning that Archer drinks less than the NHS's guideline. However, by accounting for the daily Bloody Marys that Archer has for breakfast, this number becomes 34.40 units per week, well above the NHS guideline.